Self-physical and emotional perception in rhythmic gymnastics for drop out - D'Elia, F.; Izzo, R.; Senatore, B. (Journal of Human Sport & Exercise, 2019)
In rhythmic gymnastics, very young athletes undertake a competitive activity and support workloads of four or five hours, almost unthinkable for such small girls, yet to achieve maximum results it is necessary to start at a young age and work hard. The purpose of the study is to study, in different groups of athletes (3-7 years, 8-12 years, 13-18 years) of rhythmic gymnastics, how they face emotionally and physically the physical and emotional workloads and especially if you find physical and mental well-being. The method of the study is qualitative/quantitative and the administration of 10 questions: 5 to identify the physical self-perception and 5 for the emotional one, is done anonymously. The data shows that the self-perception for physical performance is average (positive or negative and put the percentage) and the self-perception for motivation performance is average (positive or negative) and put the percentage. This data is significant for the perceptive state of the athletes to whom it is necessary to refer in order to realistically face the problem. Given the data and their significance, the study must be deepened with a more significant and detailed sample of data.